2016
DOI: 10.1103/physreve.94.043308
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase transition in coupled spin-lattice systems: A replica-exchange Wang-Landau study

Abstract: Coupled, dynamical spin-lattice models provide a unique test ground for simulations investigating the finite-temperature magnetic properties of materials under the direct influence of the lattice vibrations. These models are constructed by combining a coordinate-dependent interatomic potential with a Heisenberg-like spin Hamiltonian, facilitating the treatment of both the atomic coordinates and spins as explicit phase variables. Using a model parameterized for bcc iron, we study the magnetic phase transition i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To characterize phonon and magnon modes, we performed simulations for the system size L = 16 (8192 atoms) at temperatures T = 300 K, 800 K, and 1000 K. T = 1000 K was particularly chosen due to its vicinity to the Curie temperature of bcc iron, T C ≈ 1043 K. (A recent high resolution Monte Carlo study has revealed that the transition temperature of the particular spinlattice model used in our study to be T ≈ 1078 K [54]). Equations of motion were integrated up to a total time of t max = 1 ns, and the space-displaced, time-displaced correlation functions were computed for the three principle lattice directions: [100], [110] and [111].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…To characterize phonon and magnon modes, we performed simulations for the system size L = 16 (8192 atoms) at temperatures T = 300 K, 800 K, and 1000 K. T = 1000 K was particularly chosen due to its vicinity to the Curie temperature of bcc iron, T C ≈ 1043 K. (A recent high resolution Monte Carlo study has revealed that the transition temperature of the particular spinlattice model used in our study to be T ≈ 1078 K [54]). Equations of motion were integrated up to a total time of t max = 1 ns, and the space-displaced, time-displaced correlation functions were computed for the three principle lattice directions: [100], [110] and [111].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…220 This has been applied successfully to get the martensitic transition temperature and the stability of premartensitic phases in Ni-Mn-Ga system. 221 The recently developed spin dynamics with quantum thermostat 106 , the Wang-Landau technique to sample the thermodynamic density of states in the phase space directly 222 , and the atomistic spin-lattice dynamics are interesting to explore in the future. 223 Last but not least, magnetic materials with noncollinear magnetic ordering and thus vanishing net magnetization can also be used for caloric effects such as barocaloric 224 and elastocaloric 225 effects, it is essential to evaluate the free energy properly which has been investigated recently.…”
Section: F Magneto-structural Transitionsmentioning
confidence: 99%